2021
DOI: 10.1177/10760296211055165
|View full text |Cite
|
Sign up to set email alerts
|

Practicability of Bivalirudin plus Glycoprotein IIb/IIIa Inhibitors in Patients Undergoing Percutaneous Coronary Intervention: A Meta-Analysis

Abstract: A variety of antithrombotic drugs are used during percutaneous coronary interventions (PCIs). We aimed to investigate the practicability of the use of bivalirudin and GPIs in patients receiving PCI. We searched 7 of 629 relevant records from PubMed, the Cochrane Library, EMBASE, and Web of Science for randomised controlled trials. There were no significant differences in the rates of major adverse cardiac events (MACE) between bivalirudin plus GPI and heparin (all P  >  .05). Bivalirudin plus planned GPI wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Bivalirudin, a synthetic analog of natural anticoagulant hirudin which consists of 20 amino acid peptides, is an explicit and irreversible thrombin inhibitor with concentrationdependent competitive and non-competitive thrombin repressing effect (8,9). Unlike the UFH, bivalirudin not only realizes expectable anticoagulant outcome with linear pharmacokinetic and pharmacodynamic properties, it also achieves quicker onset and has a shortened action period; but also reduces the influence of platelet function and bleeding, which makes it a potentially alternative option for anticoagulant during PCI (8)(9)(10)(11)(12). Clinically, several randomized trials have demonstrated the non-inferiority of bivalirudin vs. UFH plus glycoprotein IIb/IIIa inhibitors regrading ischemic events, but the superiority of lower bleeding risk in PCI procedures as anticoagulant (6,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Bivalirudin, a synthetic analog of natural anticoagulant hirudin which consists of 20 amino acid peptides, is an explicit and irreversible thrombin inhibitor with concentrationdependent competitive and non-competitive thrombin repressing effect (8,9). Unlike the UFH, bivalirudin not only realizes expectable anticoagulant outcome with linear pharmacokinetic and pharmacodynamic properties, it also achieves quicker onset and has a shortened action period; but also reduces the influence of platelet function and bleeding, which makes it a potentially alternative option for anticoagulant during PCI (8)(9)(10)(11)(12). Clinically, several randomized trials have demonstrated the non-inferiority of bivalirudin vs. UFH plus glycoprotein IIb/IIIa inhibitors regrading ischemic events, but the superiority of lower bleeding risk in PCI procedures as anticoagulant (6,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%